"I let it go:" Quantifying residential guardianship intentions when witnessing wildlife poaching. (January 2023) - Kahler, Jessica S.; Reynald, Danielle M.; Gore, Meredith L.
Abstract: The need to engage communities in wildlife crime prevention is particularly salient at the poaching stage, especially in biodiverse areas where communities overlap with wildlife, and ample constraints to and concerns about formal law enforcement persist. Guardianship is a concept from criminology that examines the willingness of stakeholders to assume informal roles as protectors and intervene to disrupt crimes. While it is conceptually related to stewardship, elaborating criminology's concept of guardianship in conservation allows us to develop an understanding of situational and motivational factors, and the obstacles and opportunities for increased crime preventing interventions. We developed a Guardianship Intention Index (GII) that quantifies respondents' reported willingness to supervise, perceived ability to detect offenders, and willingness to intervene when witnessing wildlife poaching within communities ( N = 10) adjacent to or living in Bukit Barisan Selatan National Park, Sumatra, Indonesia. This allowed us to explore potential relationships between guardianship dimensions and attitudinal and demographic characteristics. Among our study population ( N = 400), we found that demographic and attitudinal dimensions affected respondents' stated willingness to intervene and varied between interveners (e.g., call authorities) and those that stated non-intervention intentions (e.g., join in, ignore, covert monitoring). However, the same respondents that reported a high intention to intervene when witnessing poaching often expressed low willingness to supervise for illegal activities in the park. Parsing out differences in guardianship behavior and attitudes influencing those behaviors provides new entry points for community-based wildlife crime prevention and may facilitate efforts to increase incentives for wildlife stewardship, more broadly.